Impacto socioeconómico y productivo de los micronegocios de la región andina (Colombia) en tiempos de pandemia por covid-19 - Jessica Ferley Domínguez-Rangel; Nixon Albeiro Zambrano-Medina; Raúl Prada-Núñez (Mundo Fesc)
With the emergence of the COVID-19 pandemic, many establishments selling products and providing services were affected by temporary closures decreed to control the spread of the virus. This led in many cases to reduced income, loss of workforce, and partial or permanent closure. This article aimed to understand the impact of the pandemic on microbusinesses in the Andean Region. To this end, a social, economic, and productive characterization was applied to 2,692 randomly selected microbusinesses in different cities of the Andean Region. The methodology used was IBM's CRISP-DM. It is concluded that microbusinesses are mostly managed by women, most of whom have basic secondary education. It was also evident that sales decreased and jobs were lost during the pandemic